Analisis Hidrologi untuk Penentuan Metode Intensitas Hujan di Wilayah Kecamatan Bogor Barat, Kota Bogor - Siti Amalia Fajriyah; Eka Wardhani (Jurnal Serambi Engineering, 2020)
Rain intensity is defined as the rainfall falls in per unit time, expressed in mm/hours. Rain determined to get the discharge flood plans in sub-districts west Bogor, Bogor. Discharge flood plan needed to take into account the drainage channel would be designed again in districts west Bogor having problems. The study aimed to determine the intensity of rainfall in west Bogor as the basic determination of the drainage channel in west Bogor. Research carried out by changing the maximum daily rainfall to rain intensity. Methods used the method Bell Tanimoto, Van Breen, and Hasper Der Weduwen which is a statistical method and produce the intensity of rain. The amount of rain obtained will be substituted into formula Talbot, Sherman, and Ishiguro, and then compared to the early rain intensity. The selection method determined based on the value of the smallest standard deviation. The result of this study showed that the method chosen to determine the intensity of rain is Van Breen Method with Talbot Formula.